Inhibition effects of tanshinone on the aggregation of α-synuclein. Issue 1 (12th October 2015) - Ji, Kaige; Zhao, Yudan; Yu, Tianhong; Wang, Zhuoyi; Gong, Hao; Yang, Xin; Liu, Yang; Huang, Kun
Abstract : Bioactive tanshinone compounds inhibit the aggregation of α-synuclein and extend the life span of a C. elegans model of Parkinson's disease. Abstract : Parkinson's disease (PD) is one of the most common neurodegenerative diseases. Lewy bodies that are formed by the aggregated α-synuclein are a major pathological feature of PD. Salvia miltiorrhiza has been used as food and as a traditional medicine for centuries in China, with tanshinone I (TAN I) and tanshinone IIA (TAN IIA) as its major bioactive ingredients. Here, we investigated the effects of TAN I and TAN IIA on α-synuclein aggregation both in vitro and in a transgenic Caenorhabditis elegans PD model (NL5901). We demonstrated that TAN I and TAN IIA inhibited the aggregation of α-synuclein as demonstrated by the prolonged lag time and the reduced thioflavin-T fluorescence intensity; TAN I and TAN IIA also disaggregated preformed mature fibrils in vitro . Moreover, the presence of TAN I or TAN IIA affected the secondary structural transformation of α-synuclein from unstructured coils to β-sheets, and alleviated the membrane disruption caused by aggregated α-synuclein in vitro . Besides, the immuno-dot-blot assay indicated that TAN I and TAN IIA reduce the formation of oligomers and fibrils. We further found that TAN I and TAN IIA extended the life span of NL5901, a strain of transgenic C. elegans that expresses human α-synuclein, possibly by attenuating the aggregation of α-synuclein. Taken together, our results suggested that TAN I and TAN IIA may be explored further as potential candidates for the prevention and treatment of PD.